Training and Internship in Japan by The Job Training Institution (Disnakertrans NTB) to Improve the Competency of Human Resources in NTB Province - Made Restu Wardani, Desak; Chandra, Edy (Jurnal Ilmiah Sumber Daya Manusia, 2026)
The gap between workforce competencies and the needs of the business and industrial world remains a fundamental issue. Many formal education graduates lack the technical and soft skills required by the current job market. Therefore, the NTB Manpower and Transmigration Office continues to promote the strengthening of vocational training, competency certification, and collaboration with the business sector to ensure that human resource development programs are more relevant and targeted. This scientific paper uses descriptive qualitative research. It is designed to provide a detailed and in-depth description of a phenomenon or situation as it occurs in a given environment. Data were collected directly through interviews, observation, and documentation. The Training and Internship Program to Japan, conducted by the NTB Manpower and Transmigration Office (LPK), plays a crucial role as a facilitator and liaison between prospective workers, training institutions (LPK), the central government, and Japanese partners such as IM JAPAN. The Manpower and Transmigration Office (Disnakertrans) is responsible for ensuring a transparent and selective recruitment process, ensuring that selected candidates are truly prepared and meet the criteria. The Disnakertrans Office begins the process with a rigorous selection process, including administration, physical tests, psychological tests, interviews, and a basic Japanese language test. The goal is to select candidates who possess not only physical and mental abilities but also the motivation and readiness to face the challenges of working abroad. This program is expected to significantly impact human resource competency in the province of West Nusa Tenggara (NTB) and create a superior and competitive workforce.